Contrasting the semantic typology biases of Deaf and hearing nonsigners in their conceptualization of time and space - Macedo, María Noel (2023)
The mental lexicon offers a window into the configuration of conceptual domains such as space and time, which has been labeled as concrete the former and abstract the latter in the current embodiment approach to cognition. Space has a phonological and semantic value in sign languages, but not in spoken languages. Additionally, the representation of time by spatial means is robust in oral and sign languages. This research asks if Deaf signers and hearing nonsigners have the same conceptual organization of those domains. In their respective languages, sixty-two participants made a repeated free word association task. These results showed that the studied populations have a little overlap in the associates evocated for each clue. The analysis of the preferences of the semantic relations of the pairs clue-associate showed a greater tendency of the Deaf signers to establish thematic relations. In contrast, the hearing participants indicated a bias toward taxonomic relations. The results suggest that the abstractness or concreteness of concepts may be modulated by factors associated with linguistic modalities. However, in this compared free association norms factors related to the language deprivation of Deaf, the asymmetries in the cross-modal language contact and cross-modal borrowing were not exhaustively controlled.